Valorização dos professores da rede municipal de ensino de Uberaba/MG (2009-2019) - Vasconcelos, Juliene Silva (2021)
The teaching profession in its essence lacks analyzes and studies regarding the movements of appreciation of the career in its extended aspect, which involves remuneration, training (initial and continuing), working conditions, professional development and social recognition. By emphasizing discussions like these, we seek to overcome the irresponsible accountability of the teacher for the failure of the public school. We believe that the direction to do that is based on the emergence of the different interventions of educational policies on teaching action, in their daily context of their search and professional practice. This exploratory and descriptive research seeks to understand how the transposition of public policies discuss teacher valorization with teachers of Elementary School I of the municipal education system of Uberaba/MG, from 2009 to 2019. The materialization of this research was based on a critical bibliographic analysis, of a dialectical nature, aiming to emphasise categories such as the restructuring of capitalism, work and the teaching profession, as well as the broad professional valorization of education workers. From the reflections arising from this movement, we seek to identify aspects of valuing the teaching career in documents, both national and municipal, through documentary research. Finally, we move on to field research, with data collection through the application of a survey (online questionnaire), in which we direct questions to teachers who have classes in the early years of Elementary Education of the municipal education system of Uberaba using a case study. The questionnaire aims to point out their understanding of the materialization of the teaching career plan, especially the manifestations around valorization, including career plan, salaries, training and other objective implications of this empirical reality. The organization of all this information allowed us to structure knowledge that confirms the lack of appreciation of the teacher in the studied context, as well as the insufficient operationalization of the policies regarding this purpose. We believe it is a work of great importance because it draws a perspective on the materialization of policies and developments in the focused space - the municipal “public school” in Uberaba/MG.